Central giant cell granuloma in a child: Surgical intervention by maintaining tooth germ : A case report - Nisha Kumari; Heena Sarangal; Disha Beniwal; Ritu Namdev (Wolters Kluwer Medknow Publications, 2021)
An intraosseous lesion of jaws called central giant cell granuloma (CGCG), is significantly found in children and young adults and most of the cases are nonaggressive, asymptomatic, and slow growing. Approximately 30% of cases show an aggressive and progressively devastating nature with tendency to recur. We present a case of slow growing CGCG in mandible in a 10-year-old male managed by curettage along with preservation of tooth germ.